Generation Z students' perceptions on the abilities, skills and competencies required in the age of artificial intelligence systems - Sorin George Toma; Oana Simona Hudea (Amfiteatru Economic, 2024)
The knowledge economy promotes the use of information and communication technology and highly skilled labour on a large scale. The past decades have witnessed a continuous fall in the importance of unskilled sectors and a rise in skilled sectors combined with the emphasis on skills and competencies. Being highly familiar with the use of technology, Generation Z students are very interested in raising their chances of employability in the current digital society. The purpose of this research was to identify and analyse Generation Z students' perceptions on the abilities, skills and competencies required in the age of artificial intelligence systems. In this respect, the authors used a quantitative research method through an online survey. A total number of 352 questionnaires from students who graduated from full-time undergraduate programs within a Romanian faculty were validated. The data were processed using the SPSS 17.0 statistical software, the subsequent viability tests and analyses involving the use of Cronbach's Alpha coefficient, the Principal Component Analysis, respectively, the correlational analysis. From a theoretical point of view, the paper contributes to the enrichment of the scientific literature regarding the new relationships between human capital and the era of artificial intelligence systems, offering a new perspective on the structure of the needed abilities, skills, and competencies in the digital society. From a practical point of view, the results of the study provide solutions for improving the educational process by adapting academic programs to the demands of the digital society. The results of the research show that, on the one hand, sensorial, cognitive, and psychomotor abilities, and, on the other hand, general knowledge, business and management, and technical skills and competencies, are playing a key role in today's era of artificial intelligence systems
Keywords: I20; I23; J24; 330; students; Generation Z; abilities; skills; competencies; artificial intelligence